Everyday Aesthetics and Photography - Thomas Leddy (Aisthesis, 2014)
Everyday photographs as well as art photographs may be aesthetically appreciated.  Although this may be most obvious in the case of advertising  it is also true for amateur photographs.  Non-art photographs play an important role in our everyday lives and should not be neglected by aesthetics. That these photographs draw much of their value (often a very personal value) from being associated with memories and musings does not make them non-aesthetic. I discuss these issues drawing on Clive Bell, Lyotard and Bourdieu with special emphasis placed such contemporary art photographers as Nan Goldin and Ed Burtynsky.